2012
DOI: 10.1093/ndt/gfr807
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate decreases the activation of NF- B reducing inflammation and oxidative damage in the kidney of rats subjected to contrast-induced nephropathy

Abstract: The current experiment suggests that NF-κB induced an inflammatory response after CIN and SB could inhibit NF-κB expression protecting against CIN in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 22 publications
4
81
0
2
Order By: Relevance
“…Other studies have observed a reduction in kidney injury in other models after SCFA treatment. 22,23 The higher protection observed after acetate treatment might be due to the composition of acetate, favoring the rapid entry of the molecule into the metabolic pathway, whereas other types of SCFAs need to Figure 6. SCFA treatment inhibits NFkb activation and nitric oxide production in epithelial kidney cell line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have observed a reduction in kidney injury in other models after SCFA treatment. 22,23 The higher protection observed after acetate treatment might be due to the composition of acetate, favoring the rapid entry of the molecule into the metabolic pathway, whereas other types of SCFAs need to Figure 6. SCFA treatment inhibits NFkb activation and nitric oxide production in epithelial kidney cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Acetate administration can also protect from colitis in the absence of microbiota, 15 whereas the administration of SCFAs in wild-type mice also protects from other diseases. 17,22,23 Despite the importance of the presence of microbiota in maintaining intestinal homeostasis 39 and preventing inflammation, it appears that an increase in the concentration of SCFAs could enhance this protection. It is already known that gut microbiota can change composition rapidly through diet alteration.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, treating Npr1 ϩ/Ϫ mice with RA and SB alone or in combination prevented the expression of matrix synthesis in the cardiac tissue, suggesting that these drugs exert protective effects over the matrix remodeling process. NF-B is a redox-sensitive transcription factor that directly regulates the expression of immediate-to earlyresponse genes, cytokines, and inflammatory molecules (38,73). It has been shown that NF-B activity is significantly increased in vitamin A-deficient mice, while RA treatment attenuates its increased activation (2).…”
Section: Discussionmentioning
confidence: 99%
“…Many stimuli relevant to kidney injury can activate NF-κB, such as high glucose, advanced glycosylation end products, cytokines, growth factors, toll-like receptors and proteinuria. Large amounts of experimental results have demonstrated that inhibition of NF-κB ameliorates inflammation, conferring a renoprotective phenotype (70)(71)(72)(73)(74).…”
Section: Sirt1 Suppresses Inflammation By Targeting Nf-κb and High-momentioning
confidence: 99%